A question of confidence - Kyomuhendo Baitwa, Jane (Technical Centre for Agricultural and Rural Cooperation, 2002)
Jane is of the new generation of information professionals: open, enthusiastic, committed, demand-responsive. Between workshops at a CTA seminar on farmers organisations, she spoke with Spore about her work, deeds and dreams. Listen in to a chat...